Etika Terang dalam Matius 5:16; antara Kesaksian Iman dan Bahaya Pencitraan Diri - Nik Anna; Markus Suwandi; Yahyo Nehemia Suyadi; Marga Diraja (PT. Penerbit Tiga Mutiara, 2025)
The growing dominance of self-image construction in modern religious practice has diminished the authenticity of faith and shifted moral orientation from God toward public approval, indicating the need for an ethical framework capable of realigning the direction of Christian witness. This study employs Matthew 5:16 as the basis for reinterpreting the ethics of light as a corrective to performance-oriented religiosity and for formulating principles of sincere, theocentric, and contextually relevant faith testimony. The research utilizes literature review and historical-grammatical exegesis of the key Greek terms φῶς (phōs), καλὰ ἔργα (kalā erga), and δοξάσωσιν (doxasōsin), drawing on academic commentaries and recent scholarly findings. The analysis demonstrates that the ethics of light is not merely a moral exhortation but a participatory ethic that positions human beings as reflectors of God’s love rather than autonomous producers of moral virtue. Authentic good works direct glory to the Father, eliminating the pursuit of social recognition and rejecting religious self-presentation. The concept of hidden righteousness emerges as a theological critique of visual culture that prioritizes visible spiritual performance, affirming instead that genuine piety grows through inner integrity and spiritual perseverance. Its relevance to the digital age is expressed through a form of faith witness that promotes justice, solidarity, and consistent spiritual character within public spaces shaped by identity curation. The study concludes that the ethics of light constitutes a spirituality of witness integrating faith, morality, and social responsibility while offering novelty through a theocentric reinterpretation of the ethics of light as a constructive critique of contemporary religious self-imaging and an ethical paradigm for cultivating authentic Christian faith in the digital era.